Corporate Governance and Sustainability in Indonesia: The Moderating Role of Institutional Ownership - Andreas - Tan; Arumega - Zarefar (Jurnal Dinamika Akuntansi, 2022)
Purpose: This paper aims to empirically investigate the impact of corporate governance on sustainability disclosure in Indonesia and explore whether institutional ownership moderates the relationship between corporate governance and firm performance.Method: This study uses panel data and regression models to test the hypothesized relationships. This study covers 2014 to 2020 for 43 listed Indonesian firms in the consumer goods sector on Indonesia Stock Exchange (IDX).Finding: The results revealed that corporate governance positively influences sustainability disclosure. However, institutional ownership is not moderate this relationship. Further, the robustness model confirmed the relationship between corporate governance and sustainability disclosure.Novelty:  This study is the first that exclusively chose institutional ownership to moderate the relationship between corporate governance and sustainability disclosure from the Indonesian perspective. Such new insights into this relationship provide helpful information to the government, academics, policymakers, and other stakeholders.